Ship safety in open ports - Paulauskas, Vytautas; Paulauskas, Donatas; Wijffels, Joep (Transport, 2009)
Ports and terminals open to prevailing winds can cause problems to moored ships with a high freeboard. Such ships, i.e. ship and berth mooring systems, have to deal with significant aerodynamic loads.This paper addresses the theoretical approach of the influence of aerodynamic loads on a mooring system for ship and investigates whether windscreens can reduce aerodynamic loads on ships in ports.First published online: 27 Oct 2010